Minat Kerja Generasi Muda Pada Sektor Pertanian di Desa Ngablak Magelang - M.Wahyu Kuncoro, Meisha Miko Yudha Prasetya, (Jurnal Pusat Studi Pendidikan Rakyat, 2024)
Agriculture is the use of natural resources to produce food. The phenomenon that occurs is a decrease from year to year in the number of workers. Data shows that there has been a shift in interest in working in the agricultural sector. Efforts to increase the interest of the younger generation in the agricultural sector require an intensive and structured policy design. This research was carried out in Ngablak village, Magelang Regency. This research uses a qualitative method with a case study approach. The research subjects were young people aged 19 to 27 years. Data analysis was carried out with 3 participants and 1 informant using purposive sampling techniques. Data collection by observation and interviews. Non-participant observation, while the interview technique carried out by the researcher was an in-depth interview using a semi-structured method. Passion research results emerged because of work motivation, attractiveness to work and work activities. External factors that influence this are HR innovation, technology upgrades and human resource improvements. Other factors include government support, namely agricultural extension officers and fertilizer subsidies. This research also indicates that the interest of rice farming family members is low in working in the rice farming sector because of minimal income. A person's passion in the agricultural sector is influenced by interest in the field of work, motivation and work activities. External factors that influence passion are HR innovation, technology upgrades. and improving human resources. The suggestion is that there is an additional variable, namely the gender variable. Suggestions for improvement for the development of agricultural technology include agribusiness development, collaboration or research with developed countries that have already used technology in agriculture.